PUBLIC SECTOR HOSPITAL SERVICE QUALITY AND PATIENT LOYALTY: MEDIATING ROLE OF PATIENT TRUST IN LAHORE, PAKISTAN (The Research of Medical Science Review, 2025)
The purpose of this study is to explore the relationship between health care quality and patients’ loyalty by using patients’ trust as a mediator. This study examines the impact of patient satisfaction, patient safety, physician performance, nursing care performance, and operational service quality on patients’ loyalty for public sector hospital. The primary data have been collected by using stratified random sampling. The questionnaires have been received from 259 respondents. The respondents are mostly consisted on patients or their attendants in a public healthcare institution in Lahore, Pakistan. The empirical results shows that there is significant impact of the patients’ satisfaction through use of mediation of patients’ trust upon patients’ loyalty. This study also contributes that there is significant influence of patients’ safety through the mediation of patients’ trust on patients’ loyalty. The study contributes that there is significant impact of perceived physician performance through mediation of the patients’ trust on patients’ loyalty. The study also contributes that there is no significant impact of nursing performance and operational service quality through mediation of patients’ trust on patients’ loyalty. Therefore, the outcomes of this research have to be further examined to make sure their stability. The findings of this research can be helpful for the management of healthcare service institutions to ensure patients' loyalty as well as their trust.